2018
DOI: 10.1098/rstb.2017.0391
|View full text |Cite
|
Sign up to set email alerts
|

The history and impact of digitization and digital data mobilization on biodiversity research

Abstract: One contribution of 16 to a theme issue 'Biological collections for understanding biodiversity in the Anthropocene'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
156
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(173 citation statements)
references
References 68 publications
(74 reference statements)
1
156
0
Order By: Relevance
“…choosing species for which there is appropriate coverage for hypothesis testing), for collecting preliminary data and for providing broader access to collections [25]. In this issue, Nelson & Ellis [69] detail the history of digitization, the research made possible by digitized collections and the biases in digital specimen data, including that few digitized records are available from Russia, India and the continent of Africa (though South Africa is an emerging leader in digitization).…”
Section: Next Generation Collections Researchmentioning
confidence: 99%
“…choosing species for which there is appropriate coverage for hypothesis testing), for collecting preliminary data and for providing broader access to collections [25]. In this issue, Nelson & Ellis [69] detail the history of digitization, the research made possible by digitized collections and the biases in digital specimen data, including that few digitized records are available from Russia, India and the continent of Africa (though South Africa is an emerging leader in digitization).…”
Section: Next Generation Collections Researchmentioning
confidence: 99%
“…Apart from the multiple advantages that digitising museum specimens has for educational, public engagement, and research purposes, as well as preventing potential damage to a collection and preserving multiple virtual copies of it (e.g., Cook et al, 2014;Antell, 2018;Nelson & Ellis, 2018), it has been recently shown how digitisation "mitigates some of the challenges associated to the dispersion of specimens" (Antell, 2018). In our particular case, the digitised photographs of the specimens, some of them showing the original Königsberg/Klebs collection numbers or tags, that had been recently made public online thanks to the "Fossil Insect Collaborative" digitisation project at the MCZ, triggered the contact between the authors of the present study and caused the subsequent developments.…”
Section: Discussionmentioning
confidence: 99%
“…scientific studies or surveys by ecological consultants), and increasingly through citizen science projects, all of which can consist of standardised surveys and/or opportunistic sightings (August et al 2015;Berry 1988;Pocock et al 2015). These data are frequently, but not always, collated locally by biological records centres (Nelson and Ellis 2018), and globally, into the Global Biodiversity Information Facility (GBIF-https://www.gbif.org/) (Robertson et al 2014). GBIF is the world's largest open-source biodiversity dataset, and currently holds nearly 1.4 billion records, comprised of over 49,000 individual datasets (as of December 2019).…”
Section: Using Wildlife-vehicle Collision Data To Inform About Speciementioning
confidence: 99%